Understanding effects of floral products on bee parasites: Mechanisms, synergism, and ecological complexity. (April 2022) - Fitch, Gordon; Figueroa, Laura L.; Koch, Hauke; Stevenson, Philip C.; Adler, Lynn S.
Abstract: Floral nectar and pollen commonly contain diverse secondary metabolites. While these compounds are classically thought to play a role in plant defense, recent research indicates that they may also reduce disease in pollinators. Given that parasites have been implicated in ongoing bee declines, this discovery has spurred interest in the potential for 'medicinal' floral products to aid in pollinator conservation efforts. We review the evidence for antiparasitic effects of floral products on bee diseases, emphasizing the importance of investigating the mechanism underlying antiparasitic effects, including direct or host-mediated effects. We discuss the high specificity of antiparasitic effects of even very similar compounds, and highlight the need to consider how nonadditive effects of multiple compounds, and the post-ingestion transformation of metabolites, mediate the disease-reducing capacity of floral products. While the bulk of research on antiparasitic effects of floral products on bee parasites has been conducted in the lab, we review evidence for the impact of such effects in the field, and highlight areas for future research at the floral product-bee disease interface. Such research has great potential both to enhance our understanding of the role of parasites in shaping plant-bee interactions, and the role of plants in determining bee-parasite dynamics. This understanding may in turn reveal new avenues for pollinator conservation. Graphical abstract: Image 1